Organizational Commitment of Teachers: A Meta-Analysis Study for the Effect of Gender and Marital Status in Turkey - Çoğaltay, Nazım (My University, 2015)
This meta-analysis summarizes the influence of Turkish teacher's gender and marital status on their perception of organizational commitment. In total, 30 independent research studies conducted across the country are investigated to analyze the relations between gender and organizational commitment, i.e., a sample group of 11,724 participants. In addition, 17 independent research studies related to marital status and organizational commitment were also collected, i.e., a sample group of 5,467. The results of random effects model show that teachers' organizational commitment is not affected by their gender or marital status. It is understood that the sample region and school level in which teachers work do not moderate this effect
Keywords: Eğitim, Eğitim Araştırmaları